Laschamp Excursion at Mono Lake? ... - Kent, Dennis V.; Hemming, Sidney R.; Turrin, Brent D. (Columbia University, 2002)
The Laschamp Geomagnetic Excursion (ca. 41 ka) and a related increase of cosmogenic nuclides provides a global tie point among sedimentary and ice core records. In the Wilson Creek Formation, Mono Lake, California, the Laschamp Excursion has not been recognized although the so-called Mono Lake excursion was found in the section with an estimated age of about 28 14C ka. However, our reevaluation of the age of the Mono Lake excursion at its type locality using new 14C dates on carbonates and 40Ar/39Ar sanidine dates on ash layers yields an estimate of 38-41 ka. This chronology and the absence of a second excursion in the Wilson Creek Formation suggest that the distinct paleomagnetic feature with negative inclinations at Mono Lake is correlative with the Laschamp Excursion. ...